Tinjauan Literatur Faktor-Faktor yang Berhubungan dengan Perilaku Seks Pranikah pada Remaja Tahun 2020-2025 Berdasarkan Teori Health Belief Model (HBM) - Almira Chiara Putri Nusantara; Luqman Effendi (Pusat Riset dan Inovasi Nasional, 2025)
Premarital sexual behavior among adolescents is a reproductive health problem influenced by various internal and external factors. The Health Belief Model (HBM) is used as a framework to understand this behavior, but previous research findings still show varying results. This study aims to analyze the contribution of the Health Belief Model components to premarital sexual behavior among adolescents based on the results of local research for the period 2020-2025. The method used was a literature review of relevant journal articles and scientific papers. The results showed that perceived vulnerability, perceived barriers, self-efficacy, and external cues to action such as media exposure and peer influence were variables that were consistently related to the main/dominant predictors of external cues to action, while perceived severity and perceived benefits showed inconsistent relationships. This study confirms that adolescent premarital sexual behavior is influenced by the interaction between cognitive, psychosocial, and environmental factors, thus requiring comprehensive and contextual reproductive health interventions.